Three-metal-atom-doped porous carbon material catalyst as well as preparation method and application thereof
By doping metal atoms such as Fe, Co, Ni in the porous carbon material catalyst, a catalyst with a high specific surface area and a unique pore structure was prepared, which solved the problems of multiple iodide shuttle, self-discharge and slow kinetics in zinc-iodine batteries, and achieved high efficiency, stability and long life of the battery.
Patent Information
- Application Number
- CN202411987493.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Zinc-iodine batteries are facing problems such as multi-iodide shuttle, self-discharge and slow kinetics on the road to commercialization, and existing catalysts are difficult to effectively solve these problems.
A catalyst with a unique porous carbon material doping is prepared by carrying metal atoms such as Fe, Co, Ni, Cu, Mn, etc. on the nitrogen-doped carbon material matrix to prepare a catalyst with a unique pore structure and high specific surface area.
This catalyst can effectively inhibit the shuttle effect of multi-iodide, improve the Coulomb efficiency and stability of the battery, reduce self-discharge phenomenon, extend battery life, and significantly improve the redox reaction kinetics of iodine.
Smart Images

Figure CN119812335A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a tri-metal atom-doped porous carbon material catalyst and a preparation method and application thereof. Background Art
[0002] In today's rapidly developing energy era, finding a reliable, efficient and environmentally friendly energy storage system has become a pressing issue worldwide. As a new type of electrochemical energy storage device, aqueous zinc-iodine batteries have become an ideal choice for renewable energy storage and grid regulation due to their inherent safety, environmental friendliness, abundant resources and low cost. However, zinc-iodine batteries still face many challenges on the road to commercialization, such as the shuttling of multiple iodides, battery self-discharge, and slow kinetics. Catalysts with high specific surface area, rich active sites and excellent electrochemical properties provide new ideas for solving the existing problems of zinc-iodine batteries. Summary of the invention
[0003] In view of this, the present application provides a tri-metal atom-doped porous carbon material catalyst and its preparation method and application. The catalyst can effectively inhibit the shuttle effect of poly-iodides and improve the coulombic efficiency of the battery; at the same time, its unique pore structure helps to reduce self-discharge and extend the battery life; in addition, the introduction of metal atoms can significantly enhance the redox reaction kinetics of iodine, thereby improving the rate performance and stability of the battery, which is of great significance to promoting the commercial development of zinc-iodine batteries and can effectively overcome the defects of the above-mentioned prior art.
[0004] In a first aspect, the present application provides a three-metal atom-doped porous carbon material catalyst, wherein the three-metal atom-doped porous carbon material catalyst comprises a nitrogen-doped carbon material matrix and three metal atoms loaded on the nitrogen-doped carbon material matrix.
[0005] Preferably, the three metal atoms are a combination of any three metal atoms of Fe, Co, Ni, Cu and Mn.
[0006] Preferably, the doping amount of the three metal atoms is 0.1-4%.
[0007] The second aspect of the present application also provides a method for preparing the above-mentioned three-metal atom-doped porous carbon material catalyst, comprising the following steps:
[0008] (1) dissolving concentrated hydrochloric acid in ultrapure water, mixing and stirring, then sequentially adding metal source XCl3·6H2O and melamine, heating and stirring until the solvent is completely evaporated to obtain powder; heat-treating the powders respectively to obtain X-C3N4 material, wherein X represents a metal atom;
[0009] (2) Repeat step (1) three times, and the metal sources added three times are different from each other, to obtain three different X-C3N4 materials respectively;
[0010] (3) Three different X-C3N4 materials are added to a Tris-HCl solution, and then dopamine hydrochloride is added, stirred at room temperature, and then filtered, washed, and dried to obtain an intermediate product; the intermediate product is pyrolyzed to obtain a trimetallic atom-doped porous carbon material catalyst.
[0011] Preferably, in step (1), the specific conditions of the heat treatment are: heat treatment temperature is 450-600°C, heat treatment time is 2-6h, and heating rate is 5-10°C / min. More preferably, it is 500°C and heating rate is 10°C / min.
[0012] Preferably, in step (2), the specific conditions of the pyrolysis are: pyrolysis temperature is 700-1000°C, pyrolysis time is 2-6h, more preferably 2h; or
[0013] In step (2), the concentration of the Tris-HCl solution is 0.5-3M; or
[0014] In step (2), the stirring time is 10-24h.
[0015] The third aspect of the present application also provides the use of the above-mentioned three-metal atom-doped porous carbon material catalyst in the positive electrode of a zinc-iodine battery.
[0016] The fourth aspect of the present application also provides a positive electrode sheet, which includes the above-mentioned three-metal atom-doped porous carbon material catalyst, a current collector, a binder and a conductive agent.
[0017] The fifth aspect of the present application also provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0018] (1) mixing the trimetal atom-doped porous carbon material catalyst and active iodine in a mass ratio of 1:1, then placing in a sealed bottle, and heat treating at 100-200° C. for 5-10 h to obtain a trimetal atom-doped porous carbon material catalyst-loaded iodine positive electrode material;
[0019] (2) The tri-metal atom-doped porous carbon material catalyst loaded with iodine positive electrode material is mixed with a conductive agent and a binder in a certain proportion, and coated on a current collector to obtain a positive electrode sheet.
[0020] The sixth aspect of the present application also provides a zinc-iodine battery, comprising the above-mentioned positive electrode sheet, negative electrode zinc sheet, diaphragm and zinc salt electrolyte.
[0021] Compared with the prior art, this application has the following beneficial effects:
[0022] The tri-metal atom-doped porous carbon material catalyst of the present application can accelerate the iodine redox kinetics while adsorbing polyiodides, inhibiting the shuttling of polyiodides, and achieving long-lasting cycle stability of aqueous zinc-iodine batteries; and the catalyst has the advantages of high specific surface area, high porosity, high conductivity, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 The adsorption / desorption isotherms of the three-metal atom-doped porous carbon material catalyst prepared in Example 1 of the present application under a nitrogen atmosphere;
[0025] Figure 2 This is a comparison chart of the electronic conductivity of the powder samples of Example 1 and Comparative Example 1 of the present application;
[0026] Figure 3 The X-ray diffraction patterns of the powder samples after iodine loading in Example 1 and Comparative Example 1 of the present application;
[0027] Figure 4 The cyclic voltammetry curves of the zinc-iodine battery assembled in Example 1 and Comparative Example 1 of the present application at a scan rate of 0.5 mV / s;
[0028] Figure 5 This is a long cycle performance diagram of the zinc-iodine battery assembled in Example 1 of the present application and Comparative Example 1 at 1C;
[0029] Figure 6 This is a self-discharge performance diagram of the zinc-iodine battery assembled in Example 1 of the present application and Comparative Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0031] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0032] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0033] Example 1
[0034] (1) Add 100 mL of ultrapure water and 20 mL of concentrated hydrochloric acid into a beaker and stir, then add 0.2 g of FeCl3·6H2O and 10 g of melamine in turn, stir at 110°C until the solvent evaporates completely, and obtain powder. Finally, place the obtained powder in a muffle furnace, keep it at 500°C for 2 h, and heat it at a rate of 10°C / min to finally obtain Fe-C3N4. Replace FeCl3·6H2O with chlorides of Co and Ni to obtain Co-C3N4 and Ni-C3N4 in turn.
[0035] (2) Add 0.5 g Fe-C3N4, 0.5 g Co-C3N4, and 0.5 g Ni-C3N4 to 100 mL of 2 M Tris-HCl solution. Then add 0.85 g C8H 12 ClNO2 (dopamine hydrochloride), stirred at room temperature for 12 hours, then the obtained product was filtered and washed. Then dried in a vacuum oven at 60°C overnight. Finally, the dried product was pyrolyzed at 800°C for 2 hours to finally obtain FeCoNi trimetallic atom-doped porous carbon material catalyst.
[0036] (3) 0.5 g of the above-mentioned tri-metal atom-doped porous carbon material catalyst was mixed with 0.5 g of active iodine, and then placed in a sealed bottle and heat treated at 100° C. for 6 h to obtain a FeCoNi tri-metal atom-doped porous carbon material catalyst loaded with iodine positive electrode material.
[0037] (4) The FeCoNi trimetallic atom-doped porous carbon material catalyst loaded with iodine positive electrode material is mixed with a conductive agent and a binder in a mass ratio of 7:2:1, coated on a steel mesh current collector, and dried at 40° C. for 12 h to obtain a positive electrode sheet.
[0038] (5) The positive electrode sheet, zinc salt electrolyte, separator, zinc salt electrolyte and zinc sheet negative electrode are assembled in sequence to form a zinc-iodine battery.
[0039] like Figure 1 As shown, the FeCoNi trimetallic atom-doped porous carbon material catalyst prepared in Example 1 has a carbon content of 893.39 m 2 g -1 The zinc-iodine battery assembled in this embodiment has a smaller polarization at 1A g -1 After 10,000 cycles at a current density of 1.34 W, the discharge capacity remained at 113.6 mAh g -1 .
[0040] Example 2
[0041] (1) Add 100 mL of ultrapure water and 20 mL of concentrated hydrochloric acid into a beaker and stir, then add 0.2 g of FeCl3·6H2O and 10 g of melamine in sequence, and stir at 110°C until the solvent evaporates completely to obtain a powder. Finally, the obtained powder is placed in a muffle furnace and kept at 550°C for 2 h at a heating rate of 10°C / min to finally obtain Fe-C3N4. Replace FeCl3·6H2O with chlorides of Mn and Ni to obtain Mn-C3N4 and Ni-C3N4 in sequence.
[0042] (2) Add 0.5 g Fe-C3N4, 0.5 g Ni-C3N4, and 0.5 g Mn-C3N4 to 50 mL of 2 M Tris-HCl solution. Then add 0.85 g C8H 12 ClNO2, stirred at room temperature for 12 hours, and then the obtained product was filtered and washed. Then it was dried in a vacuum oven at 60°C overnight. Finally, the dried product was pyrolyzed at 700°C for 2 hours to finally obtain FeNiMn trimetallic atom-doped porous carbon material catalyst.
[0043] (3) 0.5 g of the above-mentioned tri-metal atom-doped porous carbon material catalyst was mixed with 0.5 g of active iodine, and then placed in a sealed bottle and heat treated at 100° C. for 7 h to obtain a FeNiMn tri-metal atom-doped porous carbon material catalyst loaded with iodine positive electrode material.
[0044] (4) The FeNiMn trimetallic atom-doped porous carbon material catalyst loaded with iodine positive electrode material is mixed with a conductive agent and a binder in a mass ratio of 7:2:1, coated on a steel mesh current collector, and dried at 40° C. for 12 h to obtain a positive electrode sheet.
[0045] (5) The positive electrode sheet, zinc salt electrolyte, separator, zinc salt electrolyte and zinc sheet negative electrode are assembled in sequence to form a zinc-iodine battery.
[0046] The FeNiMn trimetallic atom-doped porous carbon catalyst prepared in Example 2 has a m 2 g -1 The zinc-iodine battery assembled in this embodiment has a smaller polarization at 1A g -1 After 10,000 cycles at a current density of 1.3 mAh g -1 .
[0047] Example 3
[0048] (1) Add 100 mL of ultrapure water and 20 mL of concentrated hydrochloric acid into a beaker and stir, then add 0.2 g of NiCl2·6H2O and 10 g of melamine in sequence, and stir at 110°C until the solvent evaporates completely to obtain a powder. Finally, the obtained powder is placed in a muffle furnace and kept at 600°C for 2 h at a heating rate of 10°C / min to finally obtain Ni-C3N4. Replace NiCl2·6H2O with chlorides of Cu and Mn to obtain Cu-C3N4 and Mn-C3N4 in sequence.
[0049] (2) Add 0.5 g Ni-C3N4, 0.5 g Cu-C3N4, and 0.5 g Mn-C3N4 to 50 mL of 2 M Tris-HCl solution. Then add 0.7 g C8H 12 ClNO2, stirred at room temperature for 12 hours, then the obtained product was filtered and washed. Then dried in a vacuum oven at 60°C overnight. Finally, the dried product was pyrolyzed at 700°C for 2 hours to finally obtain NiCuMn trimetallic atom-doped porous carbon material catalyst.
[0050] (3) 0.5 g of the above-mentioned tri-metal atom-doped porous carbon material catalyst was mixed with 0.5 g of active iodine, and then placed in a sealed bottle and heat treated at 100° C. for 7 h to obtain a NiCuMn tri-metal atom-doped porous carbon material catalyst loaded with iodine positive electrode material.
[0051] (4) The NiCuMn trimetallic atom-doped porous carbon material catalyst loaded with iodine positive electrode material is mixed with a conductive agent and a binder in a mass ratio of 7:2:1, coated on a steel mesh current collector, and dried at 40° C. for 12 h to obtain a positive electrode sheet.
[0052] (5) The positive electrode sheet, zinc salt electrolyte, separator, zinc salt electrolyte and zinc sheet negative electrode are assembled in sequence to form a zinc-iodine battery.
[0053] The NiCuMn trimetallic atom-doped porous carbon material catalyst prepared in Example 3 has a m 2 g -1 The zinc-iodine battery assembled in this embodiment has a smaller polarization at 1A g -1 After 10,000 cycles at a current density of 1.34 W, the discharge capacity remained at 109.2 mAh g -1 .
[0054] Example 4
[0055] (1) Add 100 mL of ultrapure water and 20 mL of concentrated hydrochloric acid into a beaker and stir, then add 0.2 g of FeCl3·6H2O and 10 g of melamine in sequence, and stir at 110°C until the solution evaporates completely to obtain a powder. Finally, the obtained powder is placed in a muffle furnace and kept at 550°C for 2 h at a heating rate of 10°C / min to finally obtain Fe-C3N4. Replace FeCl3·6H2O with chlorides of Co and Mn to obtain Co-C3N4 and Mn-C3N4 in sequence.
[0056] (2) Add 0.5 g Fe-C3N4, 0.5 g Co-C3N4, and 0.5 g Mn-C3N4 to 50 mL of 2 M Tris-HCl solution. Then add 0.85 g C8H 12 ClNO2, stirred at room temperature for 12 hours, then the obtained product was filtered and washed. Then dried in a vacuum oven at 60°C overnight. Finally, the dried product was pyrolyzed at 700°C for 2 hours to finally obtain a FeCoMn trimetallic atom-doped porous carbon material catalyst.
[0057] (3) 0.5 g of the above-mentioned tri-metal atom-doped porous carbon material catalyst was mixed with 0.5 g of active iodine, and then placed in a sealed bottle and heat treated at 100°C for 7 h to obtain a FeCoMn tri-metal atom-doped porous carbon material catalyst loaded with iodine positive electrode material.
[0058] (4) The FeCoMn trimetallic atom-doped porous carbon material catalyst loaded with iodine positive electrode material is mixed with a conductive agent and a binder in a mass ratio of 7:2:1, coated on a steel mesh current collector, and dried at 40° C. for 12 h to obtain a positive electrode sheet.
[0059] (5) The positive electrode sheet, zinc salt electrolyte, separator, zinc salt electrolyte and zinc sheet negative electrode are assembled in sequence to form a zinc-iodine battery.
[0060] The FeCoMn trimetallic atom-doped porous carbon material catalyst prepared in Example 4 has a m 2 g -1 The zinc-iodine battery assembled in this embodiment has a large surface area of 1A g -1 After 10,000 cycles at a current density of 1.3447 W, the discharge capacity remained at 134.6 mAh g -1 .
[0061] Comparative Example 1
[0062] (1) Add 100 mL of ultrapure water and 20 mL of concentrated hydrochloric acid into a beaker and mix and stir, then add 10 g of C3H6N6 and stir at 110°C until the solvent evaporates completely to obtain a powder. Finally, the obtained powder is placed in a muffle furnace and kept at 600°C for 2 h at a heating rate of 10°C / min to obtain a porous carbon material (i.e., a nitrogen-doped carbon material).
[0063] (2) 0.5 g of the porous carbon was mixed with 0.5 g of active iodine, and then placed in a sealed bottle and heat treated at 100° C. for 6 h to obtain a porous carbon-supported iodine positive electrode material.
[0064] (3) The porous carbon-supported iodine positive electrode material is mixed with a conductive agent and a binder in a ratio of 7:2:1, coated on a steel mesh current collector, and dried at 40° C. for 12 h to obtain a positive electrode sheet.
[0065] (4) The positive electrode sheet, zinc salt electrolyte, separator, zinc salt electrolyte and zinc sheet negative electrode are assembled in sequence to form a zinc-iodine battery.
[0066] Comparative Example 1: The zinc-iodine battery assembled at 1A g -1 After 6,000 cycles at a current density of 1.34 W, the discharge capacity remained at 66.17 mAh g -1 , and also has a higher self-discharge.
[0067] Comparative Example 2
[0068] (1) Add 100 mL of ultrapure water and 20 mL of concentrated hydrochloric acid into a beaker and mix and stir, then add 10 g of melamine and stir at 110° C. until the solvent evaporates completely to obtain a powder. Finally, place the obtained powder in a muffle furnace and keep it at 550° C. for 2 h at a heating rate of 10° C. / min to obtain a porous carbon material (i.e., a nitrogen-doped carbon material).
[0069] (2) 0.5 g of the porous carbon was mixed with 0.5 g of active iodine, and then placed in a sealed bottle and heat treated at 100° C. for 7 h to obtain a porous carbon-supported iodine positive electrode material.
[0070] (3) The porous carbon-supported iodine positive electrode material is mixed with a conductive agent and a binder in a mass ratio of 7:2:1, coated on a steel mesh current collector, and dried at 40° C. for 12 h to obtain a positive electrode sheet.
[0071] (4) The positive electrode sheet, zinc salt electrolyte, separator, zinc salt electrolyte and zinc sheet negative electrode are assembled in sequence to form a zinc-iodine battery.
[0072] Comparative Example 2: The zinc-iodine battery assembled at 1A g -1 After 6,000 cycles at a current density of 1.34 W, the discharge capacity remained at 68.98 mAh g -1 , while having higher polarization and self-discharge.
[0073] Test example
[0074] (1) Figure 2 As shown in the figure, the comparison of the electronic conductivity of Example 1 and Comparative Example 1 shows that the doping of metal atoms effectively improves the conductivity of the porous carbon material.
[0075] (2) Figure 3 As shown, the X-ray diffraction patterns of the powder samples of Example 1 and Comparative Example 1 after loading iodine do not have the characteristic peaks of iodine, indicating that iodine exists in an amorphous form.
[0076] (3) Figure 4 As shown, the cyclic voltammetry curves of the zinc-iodine battery assembled in Example 1 of the present application and Comparative Example 1 at a scan rate of 0.5 mV / s, the differences between the oxidation peak and the reduction peak of Example 1 and Comparative Example 1 are 63.4 mV / 82.2 mV, respectively, indicating that Example 1 has a smaller polarization.
[0077] (4) Figure 5 As shown in the long cycle performance diagram of the zinc-iodine battery assembled in Example 1 of the present application and Comparative Example 1 at 1C, Example 1 at 1A g -1 After 10,000 cycles at a current density of 1.34 W, the discharge capacity remained at 113.6 mAh g -1 , while the discharge capacity of comparative example 1 was only 66.17 mAh g after 6,000 cycles. -1 .
[0078] (5) Figure 6 As shown in the self-discharge performance diagram of the zinc-iodine battery assembled in Example 1 of the present application and Comparative Example 1, when the battery voltage is charged to 1.6V and remains stationary for 48 hours, the zinc-iodine battery assembled in Example 1 exhibits smaller self-discharge.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A tri-metal atom-doped porous carbon material catalyst, characterized in that: The three-metal atom-doped porous carbon material catalyst comprises a nitrogen-doped carbon material matrix and three metal atoms supported on the nitrogen-doped carbon material matrix.
2. The tri-metal atom-doped porous carbon material catalyst according to claim 1, characterized in that: The three metal atoms are a combination of any three metal atoms of Fe, Co, Ni, Cu, and Mn.
3. The tri-metal atom-doped porous carbon material catalyst according to claim 1, characterized in that: The doping amounts of the three metal atoms are all 0.1-4%.
4. A method for preparing a tri-metal atom-doped porous carbon material catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving concentrated hydrochloric acid in ultrapure water, mixing and stirring, then sequentially adding metal source XCl3·6H2O and melamine, heating and stirring until the solvent is completely evaporated to obtain powder; heat-treating the powders respectively to obtain X-C3N4 material, wherein X represents a metal atom; (2) Repeat step (1) three times, and the metal sources added three times are different from each other, to obtain three different X-C3N4 materials respectively; (3) adding three different X-C3N4 materials into a Tris-HCl solution, then adding dopamine hydrochloride, stirring at room temperature, and then filtering, washing, and drying to obtain an intermediate product; The intermediate product is pyrolyzed to obtain a tri-metal atom-doped porous carbon material catalyst.
5. The method for preparing a tri-metal atom-doped porous carbon material catalyst according to claim 4, characterized in that: In step (1), the specific conditions of the heat treatment are: heat treatment temperature is 450-600°C, heat treatment time is 2-6h, and heating rate is 5-10°C / min.
6. The method for preparing a tri-metal atom-doped porous carbon material catalyst according to claim 4, characterized in that: In step (2), the specific conditions of the pyrolysis are: pyrolysis temperature is 700-1000°C, and pyrolysis time is 2-6h; or In step (2), the concentration of the Tris-HCl solution is 0.5-3M; or In step (2), the stirring time is 10-24h.
7. Use of the tri-metal atom doped porous carbon material catalyst according to any one of claims 1 to 3 in the positive electrode of a zinc-iodine battery.
8. A positive electrode sheet, characterized in that: The invention comprises the three-metal atom-doped porous carbon material catalyst as described in any one of claims 1 to 3, a current collector, a binder and a conductive agent.
9. A method for preparing the positive electrode sheet according to claim 8, characterized in that: The following steps are involved: (1) mixing the trimetal atom-doped porous carbon material catalyst and active iodine in a mass ratio of 1:1, then placing in a sealed bottle, and heat treating at 100-200° C. for 5-10 h to obtain a trimetal atom-doped porous carbon material catalyst-loaded iodine positive electrode material; (2) The tri-metal atom-doped porous carbon material catalyst loaded with iodine positive electrode material is mixed with a conductive agent and a binder in a certain proportion, and coated on a current collector to obtain a positive electrode sheet.
10. A zinc-iodine battery, characterized in that: It comprises the positive electrode sheet, negative electrode zinc sheet, separator and zinc salt electrolyte as described in claim 8.
Citation Information
Patent Citations
Bimetal atom doped porous carbon material catalyst as well as preparation method and application thereof
CN114784304A
Preparation method of M-coated N-C catalyst applied to zinc-iodine battery as well as product and application of M-coated N-C catalyst
CN118198356A